Evaluation of Cytomorphological Changes in Urine Samples of Uremic Patients Undergoing Regular Hemodialysis (Iraqi Journal of Medical Sciences, 2016)
Background: Dialysis is one of the common strategies of renal replacement therapy for patients with chronic renal failure; however it harbors significant cellular changes in various body fluids.Objective: To evaluate the cellular changes in urine samples of patients undergoing dialysis.Methods: Seventy-two fresh midstream, spontaneously voided urine samples, they were included in the study. Early morning samples were excluded, Duration of dialysis was taken into consideration (short term and long term dialysis). Samples were centrifuged at 3000 round per minute for 15 minutes, the supernatants were decanted and the sediments were examined cytomorphologically.Results: The gross appearance of all urine samples was neither purulent nor hemorrhagic. Microscopically there was an excessive shedding of urothelial cells in urine samples of patients undergoing dialysis compared with samples of the control group which showed evidence of normal shedding. There were no significant cytological atypia or malignancy in all urine samples. The excessive exfoliation in the absence of significant inflammation, hemorrhagic, or cytological atypia was compared with control group.Conclusions: The study revealed that some cytological changes do occur in the urothilial cells in patients undergoing dialysis; these changes need further attention to disclose their real causes.Key words: chronic renal failure, hemodialysis, cytomorphology, epithelial exfoliation
Keywords: chronic renal failure; hemodialysis; cytomorphology; epithelial exfoliation